2020
DOI: 10.1002/lary.28992
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation of Head and Neck Cancer in Taiwan

Abstract: Objectives: Head and neck cancer (HNC) incidence has been increasing worldwide. We investigated the familial aggregation of developing HNC if a first-degree relative (FDR) is affected in a large database. Methods: This retrospective study utilized Taiwan National Health Insurance Database to assemble a cohort of all registered beneficiaries from 1997 to 2013 and identified diagnosed HNC patients with affected FDRs. Results: Of the 55,916 individuals diagnosed with HNC, 566 (1.01%) had affected FDRs. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In addition to the environmental exposures, individuals' susceptibility was investigated to delineate the complex host–environment interactions. In our previous study, familial aggregation was observed for HNSCCs including OPSCCs in a population‐based analyses, 5 suggesting the role of genetics in the process of tumor development. In oropharyngeal cancers, genome‐wide association analyses identify several loci, including rs1229984 in ADH1B , rs3828805 in HLA‐DQB1, rs4318431 nearby gene GALNT14 , rs13211972 in MUC21 , and rs34518860 in HLA‐DQA1, are correlated with patients' susceptibility and prognosis 6,7 .…”
Section: Introductionmentioning
confidence: 89%
“…In addition to the environmental exposures, individuals' susceptibility was investigated to delineate the complex host–environment interactions. In our previous study, familial aggregation was observed for HNSCCs including OPSCCs in a population‐based analyses, 5 suggesting the role of genetics in the process of tumor development. In oropharyngeal cancers, genome‐wide association analyses identify several loci, including rs1229984 in ADH1B , rs3828805 in HLA‐DQB1, rs4318431 nearby gene GALNT14 , rs13211972 in MUC21 , and rs34518860 in HLA‐DQA1, are correlated with patients' susceptibility and prognosis 6,7 .…”
Section: Introductionmentioning
confidence: 89%